Identifikasi Jenis Burung Berdasarkan Bentuk Paruh dengan Menggunakan Metode Convolutional Neural Network - Putri Iara Diandra Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Technological developments are developing so fast that it allows many applications to be made to facilitate human work. The detection system that will be developed at this time is based on the type of an object. Data in the form of images can provide some information such as type, age or other information. birds are members of a group of vertebrate animals (vertebrates) that have feathers and wings, therefore detection of bird species is very much needed considering the number of bird species. ). The steps taken before identifying bird species based on shape are image processing, grayscale, and thresholding. With this technology, one can see species or types of birds along with other information based on their beaks. This study will utilize a smartphone camera that is used to detect objects that are specifically only on the beak of birds to see the species/type to be detected